Parasitic fauna in dogs (Canis lupus familiaris) of a rural sector in the central region of Chile - Opazo, Alvaro (2019)
The aim of this study was to determine the presence of ecto- and endoparasites in a canine population located in a mountainous rural sector of the Valparaíso region of Chile. Thirty canines were subjected to clinical inspection to collect ectoparasites and faeces of the rectum. Faecal samples were analysed using the Burrow’s coproparasitic technique and the SNAP® Giardia Test (IDEXX). Results showed that 73% of canines had endoparasites by the coproparasitic technique. The helminths Toxocara canis (40%), Strongyloides stercoralis (17%), Dipylidium caninum (17%), Uncinaria stenocephala (13%), Ancylostoma caninum (7%) Trichuris vulpis (3%), and the protozoa Isospora sp (13%), Sarcocystis sp (3%), Entamoeba coli (3%) and Blastocystis sp (3%). The prevalence of Giardia sp was 17%, but it was 27% by the SNAP® Giardia (p=0.0004). Ticks were found in 25 canines (83%), identifying the species Rhipicephalus sanguineus and Amblyomma tigrinum. Likewise, 10 dogs (33%) presented fleas, identifying the species Ctenocephalides felis felis, Ctenocephalides canis and Pulex irritans.